Analysis of The Potential of Women’s Economic Empowerment in the Digital Marketing Sector - Irawati, Santi; Deffinika, Ifan; Rahmadani, Desi; Parta, I Nengah; Hashim, Norkhairiah (KnE Social Sciences, 2024)
Women’s economic empowerment refers to the process of enabling women to have broader control of their economic lives, including their access to resources, opportunities, and decision-making power. If women are empowered economically, they are better able to support themselves and their families, contribute to their communities, and support economic growth. Women entrepreneurs should implement current technology to maximize their business and marketing. By using digital applications, innovative creations can be provided uniquely and expanded into various materials. Furthermore, there are applications that help users to do independent financial management, having unique branding, global networking and promotions. Digital marketing helps to expand product reach in society and social media accelerates communication with customers. By attending workshops, joining industry associations, and participating in events or online communities, women can enrich their talents, access funding from organizations that support women entrepreneurs, and increase family economic support. On the other hand, there are some constraints faced, such as taking care of children and budgeting limitations for increasing their skills. This study was conducted to analyze twenty-five women’s potential in the digital marketing sector through counseling and training programs. They were from the local Batik home industry of 12 villages in Malang Regency, East Java province. These participants were chosen purposively from 100 members of PKK (Empowerment of Family Welfare) who participated in workshops and training local batik and have unique characteristics since their houses are located on the border of Malang city and Malang regency and their lifestyle is such that they are using a cellphone in daily life but not maximizing information from it, having social communities, but not maximizing their potencies in economics opportunities. This study used a quantitative approach. Data was collected through the questionnaire distribution to participants in training activities. Data analysis was carried out using SWOT analysis. The results showed that women’s perception and understanding of digital marketing in the research area were classified as low (80%), and this is also represented as a weakness and thread (80%). In order to solve this problem, micro, small, and medium enterprises (MSME) are suggested to collaborate with stakeholders in developing a sustainable program for digital marketing improvement, having support and access to markets from the governance. Keywords: Women Empowerment; Women Participation; Socioeconomics condition